EVALUATING PERFORMANCE MANAGEMENT PRACTICES IN CONTEMPORARY ZIMBABWE - Matombo, Grace Nomsa; Chikukwa, Samuel Tendai; Mapfumo, Mercy Rumbidzai (Current Journal of Human Resource Management (CJHM), 2023)
Fatigue, a multifaceted phenomenon, defies easy categorization due to its inherently subjective nature. It encompasses intricate interplays of psychological, social, and biological processes, manifesting as a state marked by diminished individual productivity and efficacy, often accompanied by heightened irritability. Depending on its origins, fatigue is dichotomized into acute and chronic forms, while its facets are commonly delineated into physical and mental realms. Physical fatigue entails challenges and reduced capacity for physical exertion, potentially leading to decreased stamina, compromised motor control, and a pervasive sense of unease. These effects reverberate in diminished productivity, compromised work quality, and attenuated workplace performance, and have even been linked to adversities in social interactions and activities. Conversely, mental fatigue denotes a decline in cognitive faculties and a decreased inclination to align actions with project requirements, often stemming from prior physical or mental exertion. Although fatigue is not unusual in healthy populations, its onset is notably influenced by diverse factors. Studies underscore that work stands out as the foremost contributor to fatigue, followed by familial and lifestyle elements. For example, research by Khalafi, Tangestani, and Osanloo (2014) investigating the nexus between work-induced stress and social support among hospital nurses in Tehran spotlighted the predictive role of social support in workplace stress and burnout